2011
DOI: 10.1038/nature10163
|View full text |Cite
|
Sign up to set email alerts
|

A conditional knockout resource for the genome-wide study of mouse gene function

Abstract: Gene targeting in embryonic stem cells has become the principal technology for manipulation of the mouse genome, offering unrivalled accuracy in allele design and access to conditional mutagenesis. To bring these advantages to the wider research community, large-scale mouse knockout programmes are producing a permanent resource of targeted mutations in all protein-coding genes. Here we report the establishment of a high-throughput gene-targeting pipeline for the generation of reporter-tagged, conditional allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
1,572
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,558 publications
(1,591 citation statements)
references
References 49 publications
(64 reference statements)
14
1,572
2
3
Order By: Relevance
“…Targeting was confirmed by long-range PCR (Skarnes et al 2011) and zygosity for the targeted allele was confirmed by a qPCR assay specific for the lacZ sequence. Mutants and WT littermates were housed in an environmentally controlled animal facility on a 12:12-h light:dark cycle with lights on at 07:00 h. Mice were fed Harlan Teklad global rodent diet #2918 with a composition of 18% protein and 6% fat.…”
Section: Mouse Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting was confirmed by long-range PCR (Skarnes et al 2011) and zygosity for the targeted allele was confirmed by a qPCR assay specific for the lacZ sequence. Mutants and WT littermates were housed in an environmentally controlled animal facility on a 12:12-h light:dark cycle with lights on at 07:00 h. Mice were fed Harlan Teklad global rodent diet #2918 with a composition of 18% protein and 6% fat.…”
Section: Mouse Productionmentioning
confidence: 99%
“…See Skarnes et al (2011) for a description of the targeting strategy and cell lines produced, and visit the International Knockout Mouse Consortium (IKMC; www.mousephenotype.org) or the KOMP Repository (www.komp.org) and the project webpage (www.kompphenotype.org) for a description of the specific alleles for each of the mutants with LacZ staining in this survey. For all alleles, the lacZ reporter was designed to be under the control of the native promoter of the targeted gene.…”
Section: Mouse Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such identification has focused on a specific target gene or protein, or a small set of protein complexes. Gene knockout, knockdown of gene expression, and targeted mutations are some methods for protein function identification (Recillas-Targa, 2006;Skarnes et al, 2011). Such low-throughput experiments were replaced by high-throughput experiments including genome sequencing and determination of the protein interactome.…”
Section: Computational Prediction Methods For Protein Functionmentioning
confidence: 99%
“…
The mission of the International Mouse Phenotyping Consortium (IMPC) is to systematically phenotype mice resulting from null alleles in the approximately 20,000 known or predicted protein encoded genes [1] to determine the function of each gene and the relationship to human disease. With a prediction of more than 30% of the mouse lines will either be lethal (no homozygous pups were recovered at postnatal day 14) or sub-viable (less then 12.5% of homozygous pups at postnatal day 14), an embryonic lethal pipeline including an assessment of the approximate stage of lethality, followed by 3D imaging to further analyze and archive the phenotype has been established [2].
…”
mentioning
confidence: 99%